Immunization of pregnant cows with Shiga toxin-2 induces high levels of specific colostral antibodies and lactoferrin able to neutralize E. coli O157:H7 pathogenicity - Albanese, Adriana Andrea (2018)
E. coli O157:H7 is a foodborne pathogen responsible for bloody diarrhea, hemorrhagic colitis and hemolytic uremic syndrome (HUS). The objective of the present work was to evaluate the ability of colostral IgG obtained from Stx2-immunized cows to prevent against E. coli O157:H7 infection and Stx2 cytotoxicity. Hyperimmune colostrum (HC) was obtained from cows intramuscularly immunized with inactivated Stx2 or vehicle for controls. Colostral IgG was purified by affinity chromatography. Specific IgG antibodies against Stx2 and bovine lactoferrin (bLF) levels in HC and the corresponding IgG (HC-IgG/bLF) were determined by ELISA. The protective effects of HC-IgG/bLF against Stx2 cytotoxicity and adhesion of E. coli O157:H7 and its Stx2-negative mutant were analyzed in HCT-8 cells. HC-IgG/bLF prevention against E. coli O157:H7 was studied in human colon and rat colon loops. Protection against a lethal dose of E. coli O157:H7 was evaluated in a weaned mice model. HC-IgG/bLF showed high anti-Stx2 titers and high bLF levels that were able to neutralize the cytotoxic effects of Stx2 in vitro and in vivo. Furthermore, HC-IgG/bLF avoided the inhibition of water absorption induced by E. coli O157:H7 in human colon and also the pathogenicity of E. coli O157:H7 and E. coli O157:H7Dstx2 in rat colon loops. Finally, HC-IgG/ bLF prevented in a 100% the lethality caused by E. coli O157:H7 in a weaned mice model. Our study suggests that HC-IgG/bLF have protective effects against E. coli O157:H7 infection. These beneficial effects may be due to specific anti-Stx2 neutralizing antibodies in combination with high bLF levels. These results allow us to consider HC-IgG/bLF as a nutraceutical tool which could be used in combination with balanced supportive diets to prevent HUS. However further studies are required before recommendations can be made for therapeutic and clinical applications.